AMELX and ENAM Polymorphisms and Dental Caries - Mohammad Reza Khami; Sahar Asgari; Sara Valizadeh; Jafar Karami; Arezou Rezaei; Nima Rezaei (Hindawi Limited, 2022)
Introduction. The variety of the genetic factors playing role in development of dental caries calls for further research in this regard. The aim of the present study was to investigate the differences between caries-free adults and adults with dental caries in terms of polymorphism of caries-related genes (AMELX and ENAM). Methods. The present case-control study was performed on 81 adults aged 18-24 years, 41 caries free, and 40 with a DMFT ≥ 4. A questionnaire containing background and demographic information (such as age, gender, time and type of latest dental check-ups, parent's education, oral self-care, and the place of residence in the first 12 years of life) was completed by participants at the time of examination. The blood sample was taken from each participant in the EDTA tube, and PCR was performed. Gene diversity of AMELX and ENAM genes was compared between the two groups. Results. Regarding AMELX gene, in the caries-free group 33 (80.5%) and in the group with DMFT ≥ 4, 33 (82.5%) students had TT genotype, but this difference was insignificant. For ENAM gene, in the caries-free group 34 (82.9%) and in the group with DMFT ≥ 4, 39 (97.5%) students had TT genotype, but this difference was insignificant (P value = 0.048, CI 95%:0.02-1.27, and OR = 0.145). Conclusion. There was no relationship between TT and TC genotypes of single nucleotide polymorphism of AMELX and ENAM gene and susceptibility to dental caries, but with increasing sample size, there may be a relationship between SNP of ENAM gene and being caries free.